PERANAN PENDIDIKAN PANCASILA DALAM MEMBANGUN SIKAP TOLERANSI SISWA DI SEKOLAH DASAR - Afifah, Annissa Nur; Zakiah, Linda; Sakmal, Juhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article discusses the role of Pancasila Education subjects in building tolerance attitudes in elementary school students. Through a descriptive qualitative method with a literature review data collection technique, it was found that Pancasila Education plays an important role in shaping students' character. Teachers also act as role models and the use of appropriate learning strategies is also the key to the success of learning tolerance attitudes. With a good understanding, students are expected to be able to apply tolerance attitudes in everyday life.